SURVEI POLA PEMBINAAN SEKOLAH SEPAKBOLA DI KABUPATEN BATANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the pattern of extracurricular school sports coaching in high schools in Salatiga . This study is a qualitative research approach of naturalistic descriptive analysis , while the data collection methods used by the researchers are observation , interviews , and documentation . The population used in this research that all high schools in Salatiga conducting extracurricular sports activities consisting of SMA N 1 Salatiga , Salatiga SMA N 2 , N 3 Salatiga SMA , SMA Muhammadiyah Salatiga , Salatiga 1 Christian High School , Christian High School 2 Salatiga , Satya Discourse and Christian high School . Respondents in this study were interviews of principals, waka student non-academic and extracurricular coaches at high schools in Salatiga . The results of research on patterns of extracurricular sports coaching such as: Human Resources trainer is 87.5 % with a total of 193 athletes . From the research it can be concluded that , patterns coaching conducted by the school in Salatiga City high schools for extracurricular sports is good enough . It's just a lot of factors that make all the coaching not run optimally , such as a mismatch between the talent and interests of learners, condition of facilities and good infrastructure inadequate.